Comparing Reservation Channels for Hotel Rooms: A Behavioral Perspective. Issue 1 (2nd January 2016) - Masiero, Lorenzo; Law, Rob
ABSTRACT: This paper studies the customers' selection of different sales channels for booking hotel rooms. Direct (hotel website) and indirect channels were considered, in which the latter were distinguished according to online travel agencies, destination marketing organization (DMO) website, and DMO call center. A multinomial logit model was estimated to investigate the influencing factors among a specific set of variables of interest (associated with either customer or hotel). The role of DMO as a third-party actor in booking hotel rooms was also investigated. Results indicated that hotel guest profile and hotel characteristics have different effects on the four analyzed sales channels. The active role of DMO in booking hotel rooms was found to be beneficial to the hotel industry as it attracts specific segments of customers, thus creating additional marketing opportunity. Relevant managerial implications were also outlined.